REVITALISASI KOPERASI DALAM MENINGKATKAN KONTRIBUSI PENDAPATAN ASLI DAERAH DI KOTA KENDARI - Syaputri, Sulistian; Sartono, Sartono; Muhammad Elwan, La Ode (Universitas Halu Oleo, 2019)
Revitalization of cooperatives is very necessary for cooperatives that are already felt to be alive and unwilling to die. Revitalization needs to be done by inactive cooperatives in order to become active cooperatives and active cooperatives to become larger cooperatives. This study aims to determine the Revitalization of Cooperatives in Increasing the Contribution of Local Revenue (Study in the Office, Trade, Cooperatives and Small and Medium Enterprises in Kendari City). This study used descriptive qualitative method. Data collection is done by observation, documentation and interviews. The results showed that the Revitalization of cooperatives in Kendari City has not been able to increase Regional Original Revenue. Revitalization of cooperatives in increasing Local Revenue is done in 3 ways, namely structuring business fields, structuring membership and empowering cooperatives. Of the three types of cooperative revitalization carried out in the city of Kendari, only limited to the arrangement of membership. The problem of inactive cooperatives in Kendari City is the lack of members' understanding of the meaning of cooperatives as one of the institutions to advance community welfare.